Improvement in Speed of Trains in Poor Visibility & Advancement of Train Transport Signaling Mechanism - Tandon, Shantam; Subramanian, Karthik; Moundekar, Tanmai; Khanna, Vansh (International Journal of Engineering and Technology, 2018)
The Railway system is heavily hampered by poor weather conditions like fog, smog and heavy rainfall especially in Northern India. These factors lead to poor visibility and reduces the average speed of trains which is the main reason for their delay, particularly in winter season. The average speed of the train is kept low so that the locomotive pilot can easily watch out signals and control the movement of the train. This paper focuses on techniques to boost the average speed of trains during low visibility by improving the transport signaling mechanism using wireless communication mechanisms using pulse code modulated signals.Â Â